Simplifying
12x + 10 + 3 + 8x = 0
Reorder the terms:
10 + 3 + 12x + 8x = 0
Combine like terms: 10 + 3 = 13
13 + 12x + 8x = 0
Combine like terms: 12x + 8x = 20x
13 + 20x = 0
Solving
13 + 20x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-13' to each side of the equation.
13 + -13 + 20x = 0 + -13
Combine like terms: 13 + -13 = 0
0 + 20x = 0 + -13
20x = 0 + -13
Combine like terms: 0 + -13 = -13
20x = -13
Divide each side by '20'.
x = -0.65
Simplifying
x = -0.65